2019
DOI: 10.1111/cpr.12606
|View full text |Cite|
|
Sign up to set email alerts
|

Reduced USP33 expression in gastric cancer decreases inhibitory effects of Slit2‐Robo1 signalling on cell migration and EMT

Abstract: Objectives: Gastric cancer (GC) is one of the most common cancers in the world, causing a large number of deaths every year. The Slit-Robo signalling pathway, initially discovered for its critical role in neuronal guidance, has recently been shown to modulate tumour invasion and metastasis in several human cancers. However, the role of Slit-Robo signalling and the molecular mechanisms underlying its role in the pathogenesis of gastric cancer remains to be elucidated. Materials and methods:Slit2, Robo1 and USP3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 56 publications
(155 reference statements)
1
28
0
Order By: Relevance
“…Interestingly, and in line with the role of TYW2 loss in ROBO1 down-regulation ( Fig. 3 D – G ) and in the proposed EMT inhibitory activity of this protein ( 32 , 33 ), restoration of ROBO1 expression by transfection in the TYW2 CRISPR/Cas9-deleted HCT-116 and SW480 cells rescued the phenotype, inducing the opposite effect with E-cadherin up-regulation and vimentin down-regulation ( SI Appendix , Fig. S14 A and B ).…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…Interestingly, and in line with the role of TYW2 loss in ROBO1 down-regulation ( Fig. 3 D – G ) and in the proposed EMT inhibitory activity of this protein ( 32 , 33 ), restoration of ROBO1 expression by transfection in the TYW2 CRISPR/Cas9-deleted HCT-116 and SW480 cells rescued the phenotype, inducing the opposite effect with E-cadherin up-regulation and vimentin down-regulation ( SI Appendix , Fig. S14 A and B ).…”
Section: Resultssupporting
confidence: 81%
“…Among the identified TYW2 targets, we selected the roundabout guidance receptor 1 (ROBO1) for further validation and study. ROBO1 was selected because it is reportedly lost in some colorectal tumors ( 30 , 31 ) and because of its proposed role as an inhibitor of cell migration and epithelial-to-mesenchymal transition (EMT) ( 32 , 33 ). We first validated the RNA expression levels observed in the RNA-seq approach by quantitative real-time RT-PCR, and found that the TYW2 unmethylated/expressing HCT-116 and SW480 cells expressed the ROBO1 transcript, whereas CRISPR/Cas9-mediated inactivation of TYW2 induced the loss of ROBO1 transcript levels ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Accumulated data has indicated that DUBs are significantly maladjusted in many types of cancers. [33][34][35][36] Until now, role of USP8 in many human cancers is still unknown, and this present study is the first to investigate USP8 in gastric cancer. This study showed that USP8 was overexpressed in both clinical GC tissues and cells, and USP8 overexpression was associated with certain clinicalpathologic variables, such as vascular tumor emboli, N classification and pTNM stage.…”
Section: Discussionmentioning
confidence: 79%
“…These results underline the potential of a transcriptional analysis to categorize clinical outcome. While most of the genes predicting outcome of CM have already been described as prognostic factors in other malignancies, such as CENPK [41][42][43][44][45][46] , INHA [47][48][49][50] , RPS6KL1 51 , CASP3 (Caspase 3) 52 , SERPINB1 (Serpin Family B Member 1) 53 , USP33 (Ubiquitin Specific Peptidase 33) [54][55][56][57][58][59] , TRPV4 60 and ACO2 61 , some of the predicting factors have not yet been associated to cancer prognosis, such as GPN1, SNRNP48, AAR2 and SNORA73B. Among the mentioned factors, GPN1 was the gene with the highest correlation coefficient with good clinical outcome in CM.…”
Section: Discussionmentioning
confidence: 99%